The development of non-intelligence factors among different levels of athletes in China - Liu, M.; Han, C.Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In modern competitive sports, achievement depends not only physical fitness, skills and intelligence, but also non-intelligence factors. Psychological non-intelligence factors include five basic categories: motivation, interest, emotion, willpower and character. In some sense, physical potential is limited while the psychological potential is unlimited. This study explores the status and problems of the nonintelligence factors of athletes in China, and compares the non-intelligence factors among different levels of athletes in China. Methods The study used both qualitative and quantitative methods. The subjects were a group of 25 elite athletes. Personal interviews of 22 coaches and 9 sport clinical psychologists were used and a reliable and valid instrument of measurement was developed to quantitatively measure and evaluate no non-intelligence factors. 748 athletes were also tested among different sports (3 sport categories) and different levels of athletes (3 levels). Results The qualitative analysis extracted 7 non-intelligence factors that affect the sports achievements. The results suggested that there are significant difference in the self confidence and persistence among age groups, and all 7 factors are significantly different between male and female groups. The independent test results demonstrate that there is no significant difference for each of the non-intelligence factors between skill sport category and fitness sport category, for each of the non-intelligence factors between team and individual sports. There were significant differences in motivation, self-confidence, selfadjustment between athletes from urban area and from rural areas in China. Discussion / Conclusions The environment (training, coaching, and education) and the gender of the athletes determine the level of development of athlete`s non-intelligence factors. This study provides information regarding current features of the developmental status of athletes` non-intelligence factors in China and references for psychological inquiry and selection of athletes. In the 21th century, athletes must have high skills, healthy body, content-related knowledge, strong motivations, firm beliefs, positive emotions, persistence, vision, and projection of life. This study has an important theoretical or practical significance for fully understanding and promoting the improvement of the overall quality of athletes in China.